Pericardial effusion in hypothyroidism: A case report. (December 2021) - Karki, Saurab; Rayamajhi, Rabindra Jang; Shikhrakar, Shreeja; Shahi, Sunil; Dhakal, Binaya; Khadka, Manoj
Abstract: Introduction: and importance: Hypothyroidism is an endocrine disorder with multiorgan involvement and various complications. One of the significant but less often seen complications is pericardial effusion. Since it can progress to life-threatening conditions like cardiac tamponade and hemodynamic instability, early diagnosis, and management of the pericardial effusion in hypothyroidism is a must. Case presentation: We present a case of a 35-year-old male who presented with bilateral lower limb swelling, facial puffiness, cold intolerance, fatigue, and hoarseness of voice for one week. Laboratory investigation showed high thyroid-stimulating hormone (TSH), low triiodothyronine (T3), and raised serum anti-thyroid peroxidase (anti-TPO). The lipid profile demonstrated hypertriglyceridemia. Ultrasonography of the neck revealed normal thyroid size with decreased echo texture and increased vascularity. An electrocardiogram showed low voltage complexes with sinus bradycardia. 2D echocardiography revealed minimal pericardial effusion with normal ventricular function. The patient was managed with thyroxine therapy which gradually resolved his symptoms and pericardial effusion. Clinical discussion: Pericardial effusion in hypothyroidism is due to the increased capillary permeability and albumin distribution volume and reduced lymph drainage in the pericardial cavity. Its presence in mild cases of hypothyroidism is uncommon although it can be seen in severe, long-standing hypothyroidism. Pericardial effusion in hypothyroidism, though rare, can present in mild cases and if overlooked can be fatal due to conditions like cardiac tamponade. Conclusion: With early cardiac assessment and adequate thyroid replacement therapy, pericardial effusion in hypothyroidism can be reversible at an early stage. So, pericardial effusion which can be overlooked in mild cases of hypothyroidism needs to be identified and managed early. Highlights: Hypothyroidism is an endocrine disorder with multiorgan involvement. Pericardial effusion is a notable complication of hypothyroidism, occurring due to the increased capillary permeability and albumin distribution volume and reduced lymph drainage in the pericardial cavity. The incidence of pericardial effusion is higher in severe, long-standing hypothyroidism whereas it's uncommon in early stages and mild form of hypothyroidism. If presents earlier, with early cardiac assessment and adequate treatment, pericardial effusion can be reversible at an early stage.